Web-Based Tailored Nursing Intervention to Support Medication Self-management: A Qualitative Study of the Experience of Kidney Transplant Recipients. Issue 11 (November 2019) - Côté, José; Fortin, Marie-Chantal; Auger, Patricia; Rouleau, Geneviève; Dubois, Sylvie; Vaillant, Isabelle; Gélinas-Lemay, Élisabeth; Boudreau, Nathalie
Abstract : Optimal adherence to immunosuppressive medication is essential to kidney graft success. A Web-based tailored virtual nursing intervention was developed to promote medication adherence and support self-management among kidney transplant recipients. A qualitative study was undertaken in a hospital setting in Montreal (Canada) to document how users experience the intervention and to explore medication intake self-management behaviors. To participate, transplant recipients had to be at least 18 years old and had to have completed at least one computer session of the intervention. Semistructured interviews were conducted with 10 participants (two women, eight men) with a mean age of 47.8 years. They reported receiving their latest renal transplant on average 10.6 years prior. Content analysis of the interview transcripts yielded five major themes: (1) kidney transplant is a gift from life; (2) routinization of medication intake; (3) intervention is a new and positive experience; (4) using the intervention offers many benefits; and (5) individual relevance of the intervention. Patient experience shows the intervention is acceptable and can help better manage medication intake. Results also underscore the importance of offering the intervention early in the care trajectory of transplant recipients. Web-based tailored virtual nursing interventions could constitute an easily available adjunct to existing specialized services.